Music and misogyny in the Crown of Aragon c. 1412 - Knighton, Tess (Artigrama, 2011)
Abstract Little is known about women and music in the Iberian Peninsula in the early fifteenth century, although archival documentation, such as pay records, and in some instances, correspondence, shows that women of high birth were actively involved in the patronage of musicians in the Crown of Aragon around the time of the Compromise of Caspe. One such woman was the French duchess Yolande of Bar, second wife of Joan I, who was largely responsible for establishing the primacy of French culture at the Aragonese court in the last decades of the fourteenth century, and, in particular, for the dissemination of the works of the poet-composer Guillaume de Machaut in the Iberian Peninsula. The arrival of the Trastámara dynasty in the Crown of Aragon served to consolidate established musical networks along which musicians and their repertories, both imported and local, flowed between Aragon and Castile. The strictures against women found in moralistic tracts such as Francesc Eiximenis’s Llibre de les dones (c.1396), viewed music —and specifically French song— as a deplorable aspect of feminine self-indulgence and vanity, in the same category as cosmetics, ostentatious clothing and jewellery. The vogue for French song that spread from court to convent is also reflected in allegorical commentaries such as Bernat Metge’s Lo somni (1399), where a more liberal attitude towards women who indulged in music as a pastime is presented. Such literary sources, if analysed with due care for their original function and purpose, can shed light on the performance contexts for women’s involvement with music and reflect trends in musical patronage and appreciation on their part. Resumen Se sabe poco sobre las mujeres y la música en la Península Ibérica a principios del s. XV, aunque la documentación de archivo revela que las de alta cuna desempeñaron un activo papel en el mecenazgo musical en la Corona de Aragón en tiempos del Compromiso de Caspe. Una de ellas fue la duquesa francesa Violante de Bar, segunda mujer de Juan I, responsable en gran parte del establecimiento de la primacía cultural francesa en la corte aragonesa en las últimas décadas del XIV, así como de la difusión de las obras del poeta-compositor Guillaume de Machaut en la Península. La llegada de la dinastía Trastámara a la Corona aragonesa consolidó las redes musicales existentes a lo largo de las cuales músicos y repertorios (locales y extranjeros) fluyeron entre Castilla y Aragón. Las invectivas en contra de la mujer en tratados moralistas, como el Llibre de les dones de Francesc Eiximenis, vieron en la música (en especial en la chanson francesa) un ejemplo deplorable de la autoindulgencia y vanidad femeninas, al mismo nivel que los cosméticos, la ropa ostentosa y la joyería. Pero el gusto por la chanson, que se expandió de la corte al convento, aparece en comentarios alegóricos como Lo somni de Bernat Metge, revelador de una actitud más tolerante hacia el cultivo femenino de la música como pasatiempo. Estas fuentes literarias, analizadas con el debido cuidado, pueden arrojar algo de luz sobre los contextos de la participación femenina en la música, así como acerca de la evolución de su papel como mecenas y conocedoras de la música de su época. Palabras clave Mujeres y música, mecenazgo musical, música en los conventos, Yolanda de Bar, Juan I de Aragón, Guillaume de Machaut, Francesc Eiximenis, Bernat Metge.